Nemško-slovenski stiki v slovenski toponimiji - Torkar, Silvo (Linguistica (Ljubljana), 2015)
The paper analyses eight Slovene toponyms which are the result of a language contact situation - with three of them, however, that only holds for their German counterparts. Slovene speakers to a lesser or greater extent took over German substitutions and adaptations of Slovene toponyms. This phenomenon has already been noted by Štrekelj in his analysis of the place name Činžat as a derivation from the Slovene appellative senožet. We show this too in the case of the place names Njiverce and Stoperce. It also happened that German speakers adapted or translated a given toponym, while Slovene speakers preserved their own form of the name, which then changed in accordance with Slovene sound change laws. An case in point are the place names Vižmarje and Goriča vas. Toponyms with a stem from one language and affixes from another are called hybrid or heteromorphic toponyms. The type is relatively common in the Slovene-speaking area, as exemplified by Ruperče, Pirniče, Gunclje (German proper names with the Slavic suffix (...)) or Prosnid, Jagnjed (Slovene appellative stems with the Old Friulian suffix -ed). This category also comprises the place names Vižinga, Ciringa, Temljine and the German counterpart of the Slovene oronym Šmarna gora, i.e. Kallenberg.
Keywords: allemand; geografska imena; German; hibridna imena; jeziki v stiku; langues en contact; nemščina; noms hybrides; Slovene; slovenščina; toponimi; toponymes